Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Non-Medis: Studi Kuantitatif Pada RSU Cakra Husada Klaten, Jawa Tengah - Alan Dwi Nugroho AMAYO; Wahyudiono Wahyudiono (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2026)
This study aims to analyze the influence of work discipline and work motivation on the performance of non-medical staff at Cakra Husada General Hospital, Klaten. The performance of non-medical staff is a crucial factor in supporting the operation and quality of comprehensive healthcare services. However, initial observations indicate inconsistent levels of discipline and differences in work motivation among staff. This study used a quantitative, causal-associative approach. Data were collected through questionnaires distributed to 85 respondents, non-medical staff at Cakra Husada General Hospital, Klaten, who were selected using a purposive sampling technique. Data analysis was performed using multiple linear regression using SPSS software. The results showed that work discipline had a positive and significant partial effect on employee performance (t-test 5.083 > t-table 1.989). Similarly, work motivation had a significant partial effect (t-test 2.725 > t-table 1.989). Simultaneously, both variables significantly influenced employee performance (F count 35.736 > F table 3.11) with a coefficient of determination (R2) of 46.6%. Work discipline was found to be the most dominant variable influencing performance. The implication of this study is that hospital management needs to strengthen the culture of discipline and improve the motivation system to optimize healthcare service performance.